(untitled) (Journal of Human Sciences, 2021)
The The Fezzan region is located in southwestern Libyae, and its location was a direct reason for making its history and civilization and making it a natural geographic link between the Mediterranean civilizations in the north and the desert cultures in the south. Ascientific technique known as the fugarat system(vertebrates) this has been culturally reflected on the successive agricultural development that the region witnessed in the past which made the Fezzan region go through a phenomenon associated with it represented in the continuous human migrations since ancient times until the presenttime, and this communication for med a cultural, cultural and social blend and fusion of these human components for ming one of the basic elements of the character of the Libyan desert in general, and the Fezzan desert in particular, this has been culturally reflected in the successive agricultural derelopment in the Fezzan region, through the interest in agricultural lands by providing advanced irrigation systems that may still exist until the present time, making these areas ameeting point for human migrations and staility in them despite the desert conditions. In addition to that, the region was located on the shortest roads linking the Mediterranean and central Africa, which made its influence and influence, inevitable, and this means that the Sahara and the coast were included together by a single cultural unit that extended from the southern shore of the heart of the desert, which reflects the region and its develop pment through its different ages. Fajarat is a unique irrigation system and a scientific method that consists in drawing water from the ground and distributing it through channels dug underground to evaporate it as a result of the high desert heat, which led to the existence of agricultural oases in the Fezzan vallegs that, over time, became markets, commercial and desert caravan stations. Modern archaeological evidence has confirmed the existence of Fezzan , suchas wadi Al- Ajal, wadi Al-shati, and other , which contributed to a wide agricultural renaissance in these areas. And we will talk, with the help of god, in this research about the scientific technology of irrigation systems in Fezzan(the Fugarat system).